Interactive Electronic Student Worksheet to Improve Student Learning Outcomes in Atomic Structure Material - Muhammad Husein Ashari; Sukarmin Sukarmin (Edunesia : Jurnal Ilmiah Pendidikan, 2026)
This study developed an interactive electronic student worksheet (e-LKPD) to improve learning outcomes on atomic structure using the Lee & Owen R&D model. The product was tested with 23 tenth-grade students at SMAN 1 Sambit and evaluated for validity, practicality, and effectiveness. Expert validation from two chemistry lecturers and one teacher confirmed strong content and construct validity, with modal scores of 3. In terms of practicality, 94.10% of students responded positively, and 91.11% of observed activities were relevant. Effectiveness was demonstrated through learning gains: 16 students achieved high n-gain scores (≥0.7) and 7 students achieved moderate gains (0.3–0.7). These findings indicate that the interactive e-LKPD is not only valid and practical but also highly applicable in classroom settings. Its digital, interactive format supports active learning and helps students grasp abstract scientific concepts more easily. The results underscore the potential of e-LKPD as an innovative tool in science education, particularly in facilitating student engagement and conceptual understanding. This Research contributes to the development of technology-based learning resources aligned with 21st-century educational needs.